The Effect of the Number of Fields on Radiotherapy Plans of Breast Cancer Patients in Three-Dimensionally Conformal Radiotherapy Plans: Dosimetric Studies - Zezy Bazeed (Shiraz University of Medical Sciences, 2021)
Background: The objective of this study was to compare the dosimetric outcome of plans with more fields to those with fewer ones for breast cancer patients. Method: 23 breast cancer patients were examined in this experimental study. Two groups of these patients were planned by treatment planning system. The number of beams was changed for each group, and the dosimetric parameters were calculated. The dose volume histogram (DVH) and the statistical analyses were performed for the two plans of all patients. Results: The DVH for the planning target volume (PTV) of the two techniques was estimated. Optimized plans were carried out to ensure that 95 % of the target volume takes 95 % of the dose. Based on the statistical analysis, the best coverage of dose had no relationship with the number of beams because the P-value of V105 %, V95%,V110%, Dmean, Dmax, conformity index, homogeneity index, and D5% were 0.9537, 0.9152, 0.3446, 0.8156, 0.9516, 0.7888, 0.2127, and 0.7282, respectively. The Mean ± standard error of mean for all PTV parameters was nearly the same. Also, the organ at risk had no significant difference after changing the number of beams, which means that the complication to normal tissue was nearly the same for both plans. Conclusion: The number of beams has no effect on PTV and normal tissue. Therefore, it is important for medical physicists to conduct the optimized plan without exceeding the number of beams to reduce the scattered radiation.